Going Exploring. [review] - Robson Kett, Margaret (Australian Book Review, 2003)
This article is a review of various young adult non-fiction, including: Mary Malbunka, "When I was Little, Like You"; Jesse Martin with Jon Carnegie, "Dream On: The Journey of Kijana – Making it Happen"; John Nicholson, "Animal Architects"; and Coral Tulloch, "Antarctica". Australia Council, La Trobe University, National Library of Australia, Holding Redlich, Arts Victoria